Detection and identification of chloramphenicol acetyltransferase gene in aeromonas isolates by multiplex polymerase chain reaction - Chua, K.H.; Radu, S.; Ismail, S.; Hassan, E.H. (2005)
A total of 37 Aeromonas isolates were isolated from retail fish in Malaysia wet market. In this study, the bacteria were tested for their haemolytic activity and susceptibility to antimicrobial agents. Twenty one (57) Aeromonas isolates showed positive haemolysin activity in this study. Six antimicrobial agents were used in this study and all the Aeromonas isolates were found resistant to at least one antibiotic, and 15 of them (41) were multiresistant. Multiplex polymerase chain reaction was another approach used to detect the existence of chloramphenicol resistance gene in Aeromonas in this study. The chloramphenicol acetyltransferase (cat) gene was detected in 16 Aeromonas isolates. Nine of the Aeromonas isolates (56) carried cat II gene, while 1 (6), 2 (13), and 4 (25) of the remaining isolates carried cat I, cat III, and cat IV gene respectively.